The Effect of Communication, Organizational Culture, and Compensation on Employee Performance at PT. Lingkar Organik Indonesia - Alwi, Nopirin (PT FORMOSA CENDEKIA GLOBAL, 2025)
Human Resources (HR) plays a role in organizational success. Facing global competition and rapid technological change, strategic HR management is key for organizations to maintain competitiveness and achieve sustainability. This study analyzes the effects of communication, organizational culture, and compensation on employee performance at PT. Lingkar Organik Indonesia. Multiple linear regression analysis was employed. Results indicate that communication (0,742) and organizational culture (0,623) have no significant impact on employee performance. Conversely, compensation significantly influences performance (0,000), contributing to a 49.8% improvement. Simultaneously, these three variables significantly affect employee performance. These findings emphasize the crucial role of compensation policies in enhancing employee performance